(untitled) (Bangladesh Journal of Animal Science, 2016)
Livestock keeping at urbanized areas is increasing folds in rate now-a-days in Bangladesh. To characterize the urban livestock keeping practices and its implications on public health and environmental issues in Mymensingh, Gazipur and Shariatpur municipality, Bangladesh, a questionnaire survey was carried out. Ninety livestock keepers were freely characterized and data were obtained through interview. Data were analyzed using percentage and mean. Age does not have any role in keeping livestock at municipal areas. Majority (73%) of the respondents have at least primary education. Male dominates in keeping livestock than female. Local political leader kept the highest number of animals then self-employer or trader takes the second position. Dairy cattle share a lion number (67%) over other species. Ninety five per cent (95%) available breeds in municipal areas are crossbred and the rest is indigenous. More than 75% livestock holders keep their animals over 3 years and only 6% keepers sell their animals within 6 months. Most of the livestock keepers (56%) use their calf as replacement stock. The majority (66%) of the livestock depends on grazing and scavenging for feed from government and municipal lands, unfenced open land, roadsides, rubbish dumps. Most of the livestock owner (66%) does not supplement to their animals with feeds other than free scavenging throughout the rearing time. Most of the farmers (85%) have temporal shed for sheltering their animals during night time. Almost 78% flying herds available in municipal areas drink water from drainage line. Disease outbreaks are 21%, 18%, 17%, 16%, 13%, and 10% of ecto-parasite, mastitis, helminthosis, lumpy skin disease, wounds, and diarrhoea. 14% livestock owner follow vaccination program to keep better their animals from viral or bacterial infections. All the respondents (100%) are aware that livestock keeping could have a negative effect on urban health and environment. More than 50% of the respondents choose dung and urine disposal, malodor and blocked roads are the major damages caused by livestock. Strategies for controlling the damages were as follows: awareness through broadcasting documentary via mass media (4.33), regular health check via veterinary services (3.96), keeping database and regular updated of livestock keepers (3.82), proper disposal of waste (3.69), strengthening rules and policy development for local authority (3.61), reducing numbers of animal (3.48), provision of extension services (3.47), cleaning vicinity daily (3.32). There were some measures taken from public interviewing which need to amend for keeping health and environment free from diseases and pollution. Bang. J. Anim. Sci. 2016. 45 (1): 44-51